Effects of a Novel Weeding and Fertilization Scheme on Yield and Quality of Rice - Yangjie Shi; Xinhui Cheng; Xiaobo Xi; Wenan Weng; Baofeng Zhang; Jianfeng Zhang; Ruihong Zhang (Agronomy, 2023)
This study aimed to assess the feasibility of a novel weeding and fertilization scheme, namely, mechanical weeding plus a one-time deep application of a reduced amount of slow-release fertilizer for rice cultivation. The effects of the weeding and fertilization method on rice yield and quality were investigated using a split plot test as the research method. Two weeding methods, namely, chemical weeding (CW) and mechanical weeding (MW), and four fertilization methods were tested, including the conventional fertilization method (quantitative split broadcast application of fast-release N fertilizer (CK)), the quantitative split broadcast application of 80% fast-release N fertilizer (LCK), the one-time base application of slow-release fertilizer (SR), and the one-time deep application of 80% slow-release fertilizer (LSR). The results showed that the rice yield under MW with LSR treatment can maintain a high level—higher than 9.2 t ha−1 per year. This was attributed to the slow-release fertilizer and deep fertilization, which increased the number of stems and tillers in the pre-fertility and spike rate, respectively, resulting in a high panicle number with a 20% reduction of N fertilizer. Furthermore, mechanical weeding improved the seed-setting rate, resulting in a higher number of grains per panicle, a higher panicle number, and an increased thousand-grain weight, thereby maintaining a high yield. At the same time, the quality of rice under MW with LSR treatment improved, specifically reflected in the significant improvement of the processing and appearance quality of rice, a slight increase in protein content, and a reduction in the amylose content, thereby improving its nutritional quality while maintaining good cooking quality.